Utilization of food waste hydrolysate for microbial lipid and protein production by Rhodosporidium toruloides Y2. Issue 3 (26th July 2016) - Zeng, Yu; Bian, Delong; Xie, Yi; Jiang, Xiaolong; Li, Xiang; Li, Panyu; Zhang, Yongkui; Xie, Tonghui
Abstract: BACKGROUND: Food waste has great potential for biotech processing but most waste is subject to traditional disposal methods, losing its value. To alleviate economic and environmental concerns, the hydrolysate of food waste could be utilized for biolipid and protein production by Rhodosporidium toruloides Y2. RESULTS: The biomass, lipid production and protein production reached 32.1 g L −1, 7.3 g L −1 and 7.0 g L −1, respectively. The composition of fatty acids and amino acids indicated that R. toruloides Y2 grown in food waste hydrolysate had the potential to be feedstock for biolipid and microbial protein production. Model prediction using the Logistic, Luedeking‐Piret equation and modified Luedeking‐Piret equation could estimate the growth, lipid production and reducing sugar utilization of R. toruloides Y2 in food waste hydrolysate. CONCLUSION: The alternative proposed for converting food waste into microbial biomass is applicable. Food waste hydrolysate is suitable for lipid and protein production by R. toruloides Y2, without any additional nutrition or detoxification procedure. © 2016 Society of Chemical Industry